2009
DOI: 10.1080/07420520802686331
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Pattern of Wheel‐Running Activity of a South American Subterranean Rodent (Ctenomys cf knightii)

Abstract: Circadian rhythms are regarded as essentially ubiquitous features of animal behavior and are thought to confer important adaptive advantages. However, although circadian systems of rodents have been among the most extensively studied, most comparative biology is restricted to a few related species. In this study, the circadian organization of locomotor activity was studied in the subterranean, solitary north Argentinean rodent, Ctenomys knightii. The genus, Ctenomys, commonly known as Tuco-tucos, comprises mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 42 publications
7
34
0
17
Order By: Relevance
“…One such animal is the South American solitary burrowing rodent, Ctenomys knightii , commonly known as the Tuco-tuco. These rodents show circadian rhythms of activity both in laboratory conditions (Valentinuzzi et al 2009) and when brought into the lab directly from the field (Tomotani et al 2012), again demonstrating the presence of a circadian system in a subterranean animal. However, even pulses of light can entrain circadian clocks (Carr and Whitmore 2005), and light-sampling behaviour, even to less than 3.5 % of the total light period, is a sufficient entraining signal for nocturnal rodents (Decoursey 1986; Decoursey and Menon 1991).…”
Section: A Review Of Rhythmic Physiology Research In Animals From Arrmentioning
confidence: 93%
“…One such animal is the South American solitary burrowing rodent, Ctenomys knightii , commonly known as the Tuco-tuco. These rodents show circadian rhythms of activity both in laboratory conditions (Valentinuzzi et al 2009) and when brought into the lab directly from the field (Tomotani et al 2012), again demonstrating the presence of a circadian system in a subterranean animal. However, even pulses of light can entrain circadian clocks (Carr and Whitmore 2005), and light-sampling behaviour, even to less than 3.5 % of the total light period, is a sufficient entraining signal for nocturnal rodents (Decoursey 1986; Decoursey and Menon 1991).…”
Section: A Review Of Rhythmic Physiology Research In Animals From Arrmentioning
confidence: 93%
“…Freshly captured animals express rhythms in constant conditions, with periods very close to 24 hours, which strongly indicate aftereffects of a previous entrainment (Tomotani et al, 2012). We have also confirmed that the tuco-tucos' circadian rhythms can be synchronized in the laboratory by artificial light/dark cycles, via entrainment of a circadian oscillator (Valentinuzzi et al, 2009). However, the participation of light information for entrainment in the field remained to be confirmed.…”
Section: Testing Entrainment To a Model Light Exposuresupporting
confidence: 60%
“…Our initial laboratory studies with this tuco-tuco species revealed marked daily rhythms of activity in the running wheel (Figure 1.2), with wheel revolutions concentrated in the dark phase (Valentinuzzi et al, 2009). The rhythm persisted in constant lighting conditions and was synchronized to artificial daily light/dark cycles.…”
Section: Circadian Rhythms In Subterranean Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Não somente em organismos fotossintetizantes, mas para qualquer modelo tal conceito é essencial, um exemplo são as análises do comportamento de camundongos em rodas de exercício que registram ao longo de meses a frequência da atividade dos animais submetidos a diversas condições. (CASIRAGHI et al, 2012;VALENTINUZZI et al, 2009), utilizando o menor esforço possível do observador.…”
Section: Ensaio Enzimático Da Nrunclassified